Access to Finance and Its Impact on the Growth of Very Small Family Businesses in Nepal - Aryal, Khimananda; Danai, Sadhu Ram (Jana Adarsha Research Journal, 2026)
Very Small family enterprises form an important part of the informal economy in Nepal and contribute much to job creation, household income and local economic activities. However, accessing formal financial services is a major challenge for these businesses and may hinder their expansion and survival. This article analyses the effect of access to finance on the performance of micro family enterprises in Chitwan district, Nepal. Descriptive and analytical design was used in data collection among 75 family-run enterprises through semi structured questionnaires by trained enumerators, considering respondents with diverse literacy levels. The research investigates the first sources of funds and measures their access to finance as well as investigates the link between accessibility and growth indicators such as sales growth, profit growth and asset buildup. The results indicate that majority of the businesses rely on personal savings and other informal lenders, except for formal finance which is not accessed possibly due to high collateral requirement, complex procedures and high interest rate. Correlation and regression show that financial access affects positively to the growth of business, revealing the ability of financial accessibility to improve asset accumulation and efficiency in operation. The study underscores the call for less cumbersome loan processes, wider microfinance and cooperative penetration along with focused financial literacy support in order to promote growth and sustainability of very small family businesses in Nepal.